Brain-targeted polymeric nanoparticles: in vivo evidence of different routes of administration in rodents. (September 2013) - Tosi, Giovanni; Ruozi, Barbara; Belletti, Daniela; Vilella, Antonietta; Zoli, Michele; Vandelli, Maria Angela; Forni, Flavio
Aims, materials & methods: The capacity of polymeric nanoparticles (NPs) to reach the target regardless of the administration route is a neglected field of investigation in pharmaceutical nanotechnology. Therefore, after having demonstrated in previous studies that glycopeptide-engineered NPs (g7-NPs) were able to reach the brain after intravenous administrations in rodents, this article aims to evaluate whether they can reach the CNS when administered by different routes.Results & conclusions: The confocal microphotographs on murine brain sections showed the capability of g7-NPs to reach the target also after intraperitoneal, intranasal and oral administrations. This could open new vistas for the future application of g7-NPs in the therapeutic treatment of CNS diseases. Original submitted 19 April 2012; Revised submitted 3 September 2012; Published online 8 April 2013